SPATIO-TEMPORAL VARIATION OF AMBIENT PARTICULATE MATTER POLLUTION IN RAJASTHAN FROM 2018 TO 2022 - Prerana Shakti; Ashutosh Kumar Pandey (International Educational Journal of Science and Engineering, 2025)
In late 2019, World Health Organization (WHO) affirmed coronavirus disease (COVID-19), prompting global lockdowns. The present study assessed impact of lockdowns on fine (PM2.5) and coarse (PM10) particulate matter and compared them with unlock phases across major cities, Rajasthan. The air quality stations are established and monitored by the Central Pollution Control Board (CPCB), New Delhi, as part of National Ambient Air Quality Monitoring Series (NAAQMS). Spatio-temporal fluctuations in PM2.5 and PM10 concentrations were analyzed during lockdown periods in 2020 and 2021, compared with corresponding periods of unlock phases in pre-lockdown (2019) and post-lockdown (2022). Results showed large PM2.5 and PM10 reductions (by 15–64% approx.) during first lockdown in 2020, due to stringent nationwide restrictions. Whereas, second wave lockdown in 2021, characterized by more relaxed and less restrictions, showed comparatively lower PM2.5 and PM10 reductions (approx. 7–33%). Hence, maximum reduction occurred during first wave 2020 when anthropogenic activities were most restricted compared to second wave lockdown due to liberation provided in second wave. Notably, during both lockdown periods, PM₂.₅ and PM₁₀ concentrations remained below the NAAQS thresholds of 60µg/m³ and 100µg/m³, based on 24-hour average, in all study locations. The study concludes that traffic restrictions and short-term lockdowns can mitigate particulate pollution. Policymakers can utilize the findings of this investigation to implement essential guidelines for mitigating air pollution emissions.